Pengaruh Rasio Likuiditas, Solvabilitas, dan Aktivitas Terhadap Profitabilitas Pada Perusahaan Sub Sektor Otomotif Yang Terdaftar Di BEI Tahun 2020-2023 - Putri Latifatul Azizah; Edi Murdianto; Agung Pambudi Mahaputra (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to examine the influence of financial performance ratios—namely, the liquidity ratio (Current Ratio/CR), solvency ratio (Debt to Asset Ratio/DAR), and activity ratio (Total Asset Turnover/TATO)—on the return on assets (ROA) of companies in the automotive sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. Employing a quantitative research approach with purposive sampling, the study focuses on automotive sector companies that met specific criteria over the observed time span. Data analysis was conducted using EViews version 13 software, and the methodology included descriptive statistics, panel data estimation, classical assumption tests, panel data regression analysis, t-tests (for partial effects), F-tests (for simultaneous effects), and coefficient of determination (R²) tests. The partial test results reveal that the liquidity ratio (CR) has a negative but statistically insignificant effect on ROA, indicating that higher liquidity does not necessarily enhance profitability. Similarly, the solvency ratio (DAR) demonstrates a negative and insignificant effect on ROA, suggesting that increased debt levels are not significantly associated with lower returns. In contrast, the activity ratio (TATO) has a positive and significant effect on ROA, implying that better asset utilization contributes positively to profitability. When tested simultaneously, the combination of CR, DAR, and TATO shows a positive and significant influence on ROA, indicating that these financial ratios collectively impact the profitability of automotive companies. These findings contribute to a deeper understanding of how internal financial indicators relate to profitability in the automotive sector and can inform management decisions and investor evaluations.